Gender, Religiosity, Love of Money, and Ethical Perception of Tax Evasion - Michael Ardho Dewanta; Zaky Machmuddah (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2019)
ABSTRACTThis study aims to examine the effect of gender, religiosity, and love of money on ethical perception of tax evasion. The population of this study consist of undergraduate accounting students of private universities in Semarang,Central Java, Indonesia. Quota sampling method was utilized with total samples of 100 students. The data was collected using questionnaire and distribution period was three months from October-December 2017. Data analysis was performed using the Structural Equation Model (SEM) and Partial Least Squares (PLS) 3.0. The results of analysis showed that gender has no effect on religiosity and love of money. Meanwhile gender, religiosity, and love of money simultaneously affect the ethical perception of tax evasion. The results also unveil that love of money and religiosity cannot mediate the relationship between gender and ethical perception of tax evasion among undergraduate students. ABSTRAKPenelitian ini bertujuan untuk menguji pengaruh gender, religiusitas, dan kecintaan terhadap uang pada persepsi etis atas penggelapan pajak. Populasi penelitian ini terdiri dari mahasiswa sarjana akuntansi dari universitas swasta di Semarang, Jawa Tengah, Indonesia. Metode pengambilan sampel menggunakan metode quota sampling n dengan jumlah sampel 100 siswa. Data dikumpulkan dengan menggunakan kuesioner dan periode pengumpulan data adalah tiga bulan dari Oktober-Desember 2017. Analisis data dilakukan dengan menggunakan Structural Equation Model (SEM) dan Partial Least Squares (PLS) 3.0. Hasil analisis menunjukkan bahwa gender tidak berpengaruh pada religiusitas dan cinta uang. Sementara itu gender, religiusitas, dan cinta uang secara simultan mempengaruhi persepsi etika atas penggelapan pajak. Hasil penelitian juga menunjukkan bahwa kecintaan terhadap uang dan religiusitas tidak dapat memediasi hubungan antara gender dan persepsi etis penghindaran pajak di kalangan mahasiswa sarjana.